Numerical investigation of the hybridisation mechanism in fibre reinforced hybrid composites subjected to flexural load - Kalantari, M.; Dong, Jonathan; Davies, Ian (Elsevier, 2016)
© 2016 Elsevier LtdWhilst the presence of a hybrid effect for the flexural strength of hybrid polymer matrix composites has been noted by several researchers, the reasons behind such a phenomenon remain unclear. In this work the authors have investigated the effect of hybridisation on the flexural strength of carbon/glass fibre reinforced epoxy hybrid composites with the aim of elucidating the mechanisms behind the hybrid effect. Classical lamination theory (CLT) and finite element analysis (FEA) were employed to determine the stress distribution within the composites with the maximum allowable load at first ply failure (FPF) and apparent flexural strength being determined based on four commonly used failure theories, namely, maximum stress, maximum strain, Azzi-Tsai-Hill and Tsai-Wu. Using the results of this analysis, general rules for the improvement of flexural strength in hybrid composites were proposed. Through application of these rules it was shown that a positive hybrid effect could be achieved for the flexural strength in both unidirectional and bidirectional hybrid composites when an optimal stacking configuration was used. Furthermore, the flexural strength predicted by the different failure theories was compared with it being noted that the strength obtained using the Tsai-Wu failure theory was significantly different from the strength obtained by other theories under certain circumstances, in particular for situations when the laminas contained different angles and/or materials. Overall it is hoped that the explanation of the mechanisms behind the hybrid effect of flexural strength together with the general design rules outlined in this work will lead to the improved optimization of hybrid composites.